Pengaruh Penjualan Sisa Hasil Produksi Terhadap Pendapatan di PT Dynacast Indonesia - Kenny Lauda; Seto Sulaksono Adi Wibowo (Politeknik Negeri Batam, 2015)
This research was conducted at PT Dynacast Indonesia. The purpose of this research is to determine whether the sales process scrap against earnings in PT Dynacast Indonesia has the accounting treatment similar to what I learned as I went to college in the country Batam Polytechnic. The analysis that I will discuss in this study is to compare the sales procedure and admission records that I have learned in college with the applicable procedures and record keeping in PT Dynacast Indonesia.